PROCESS AND SYSTEMS Afternoon ward rounds: bad for patients, bad for doctors?. Issue 2 (2019) - Carpenter, Alexander; Vora, Sona M; Kestenbaum, Samantha; Thompson, Ameeka; Devine, Mark; Tenison, Emma; Quicke, Eleanor; Liang, Kate; Deibel, Francesca
No abstract available